Tupac [videorecording (DVD)] : the lost prison tapes : uncensored & uncut - Peters, Ken; Shakur, Tupac, 1971-1996 (Flatiron Film : Distributed by New Video, 2010)
"Featuring an uncut and never-before-seen interview at the Clinton Correctional Facility, 'Tupac Shakur, uncensored and uncut : the lost prison tapes' presents a raw look into Tupac's world, as the rapper riffs on topics ranging from his involvement with gang life to prisons in America to his relationship with his mother. What emerges is a moving self-portrait of an artist who sees himself as fundamentally misunderstood: he may have diagnosed thug life, but he didn't invent it, and he is determined to uplift - not destroy - the black community."--Container.